Ethnographic Study of Perspective and Attitude of Breastfeeding Mothers Towards the use of Elaeis Guineensis Sap As Galactagogue Among Igbo Women of Southeastern Nigeria - Okamkpa Jude Chikezie; Anibeze Ikechukwu Chike; Ozor Ikemefuna Ignatius; Ikenna Kingsely Ndu; Uchenna Anthony Umeh (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: As an age-old traditional practice, nursing mothers from southeastern Nigeria use the Elaeis guineensis sap (from the oil palm tree also referred to as palm wine) to induce and sustain lactation a few hours after delivery. This practice is still ongoing to date, despite the scarcity of clinical data supporting its efficacy and safety. This study aimed to generate preliminary data on the prevalence, perceptions, and behaviors related to the use of Elaeis guineensis sap as a galactagogue.